Peran Metode Kumon Dalam Meningkatkan Hasil Belajar Secara Mandiri Pada Raudhatul Athfal - Irma Hermawati; Siti Qomariyah; Cucu Saadah Nursaidah (LP3M KH Yazid Karimullah Institute, 2023)
This study aims to describe the increase in learning ability students in the scope of cognitive development at Raudhatul Athfal Al Ikhlas through the application of the Kumon method.Student learning ability within scope cognitive development is not as expected ,because the ability to recognize facts,understand concepts,and carry out student procedures is not yetachieve the expected indicators.This research is an action research class. The subject of this study was one teacher and 18 group B students consisting of 8 male students and 10 female students.While the inner object of this study is the application of the Kumon learning method and learning abilities within the scope of cognitive development. Data collection was carried out usingobservations,dokumentationand tests. The test is carried out at the endof the lesson.After obtaining data on students cognitivelearning abilities before and after the action,then the research analyzed the data. The data analysis technique used is descriptive qualitative analysis with percentages. The results showed that students “cognitive learning abilities increased from before the action,cyts cle I and cycle II. Obtained results of cognitive learning ability Before action.3 students or 16,66% of students who reached the minimun sufficient category,1 student or 0,05 % reached the less category,then 14 studen or 77,77% of students were in the failedcategory in the action cycle I it increased to 6students or 33,33% reaching the minimum sufficient category ,and 6 students or 33,33%were in the less categorywhile 6 other students or 33.33% were still in the failed category. After corrective action was taken in cycle II ,5 student or 27,77% reached the verygood category , then 6 students or 33,33% achieved the good category,then 5 students or 27,77% were in the sufficient category,and 2 students or 11,11% were in less category. So the learning ability in the scope of cognitivedevelopmen has reached the expected indicators, namely 75% of Students are at leastin the minimal sufficient category. Based on the results obtained,there is an increase in learning abilites in the scope of students cognitive development before the Kumon method is applied and after the kumon method is applied. So it can be concluded that the application of the kumon method can improve learning abilities in the scope of cognitive development of group B RA AL IKHLAS Students in Sukabumi City.